Image Segmentation and Analysis of Pore Network Geometry in Two Natural Sandstones - Thomson, Paul-Ross; Aituar-Zhakupova, Aizhan; Hier-Majumder, Saswata (Frontiers in Earth Science, 2018)
We report the results of pore-network analysis of high resolution synchrotron microtomographic images of Fontainebleau and Berea Sandstones. We segment the gray-scale images of the rocks into constituent phases, and analyze the geometry of the pore network. The network consists of pores situated at the corner of grains and serve as the junction between elongated throats along grain edges. Our analysis indicates that the number of pores, their median coordination number, and fraction of connected pore space increases with an increase in porosity. In contrast, the width and length of throats decrease with an increase in total porosity. In each sample, the coordination number of pores is directly related to the radius of the pores, while the length of throats are also positively correlated with the throat radius. The permeability determined from the images increase with the total connected porosity of the samples and there is a change in the modeled permeability for each sample with flow direction. We observe that the dimensionless coefficient of variation of the throat lengths in all samples are nearly uniform around an average value of 0.64. The coefficient of variation of throat radii are generally higher than that of the radius of pores.